The Principal’s Role in Improving Teacher Competence in Madrasah Aliyah - Al Qadri, Miftahul Haq; Suyatno, Suyatno; Sulisworo , Dwi (International Journal of Educational Management and Innovation, 2023)
A principal, as a leader, has the important role in improving teacher competence. Teachers, who have significantly good competence, can improve their in-class learning quality. This research aims to describe the principal’s role in improving teacher competence in Madrasah Aliyah of Islamic Centre Bin Baz Yogyakarta (MA ICBB). The research method used qualitative research with a case study. Data were collected through interview, observation, and documentation. The subjects consisted of 7 sources, a school principal and 5 teachers. The data analysis technique was data collection, data reduction, data representation, and conclusion. Data validity was obtained from triangulation technique. The research result showed that 1) a principal encouraged and provided the opportunities for teachers of MA ICBB to participate in trainings and seminars inside or outside school to increase pedagogic competence; 2) a principal controlled and supervised behavior and performance of teachers for improving teacher personality competence; 3) a principal conducted final semester evaluation meeting that was aimed to invite teachers in the discussion forum concerning on phenomena occurred, that was obtained from interaction and analysis of teachers toward all students in MA ICBB to enhance teacher social competence; and 4) a principal provided the opportunity for all teachers to continue higher study, attend seminars, as well as he provided information and motivation to teachers to improve teacher professional competence.